Utilización de biosorbentes para la remoción de níquel y plomo en sistemas binarios. - Tejada, C.; Herrera, A.; Ruiz, E. (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The competitive adsorption of Pb(II) and Ni(II) onto yam peel and palm bagasse was systematicallyinvestigated in single and binary metalic systems. The studies were carried out in batch systems, by taking the pH and particle size as fixed values. All measures of metals in aqueous solution were carried out by atomic absorption. In single system, it was observed for both metals the adsorption equilibrium following the Langmuir and Freundlich models reached a maximum adsorption capacities of about 362.45 mg/g for nickel and 68.14 mg/g for lead, by using the yam peel. Moreover, a maximum adsorption capacity of about 162.64 mg/g was determined for nickel and 90.28 mg/g, obtained for lead by using palm bagasse. In the binary system, the combined action of the metals was found to be antagonistic, even if, the lead sorption was significantly increased onto yam peel in aqueous nickel solution.